P17.25 Impact on compliance with the change of first line anti-retroviral drug regimens among patients attending anteretroviral therapy clinics in blantyre, malawi. (13th September 2015) - Gadama, Y; Sheikh, S; Chasela, P
Abstract : Introduction: Change of any drug regimen impacts on compliance. Malawi changed the first line ARV regimen from stavudine-based (stavudine + lamivudine + nevarapine) to tenofovir-based regimen (tenofovir + lamivudine + efavirenz) because the former was associated with adverse side-effects and poor compliance. This study aimed at assessing the impact of the new ARV regimen on compliance. Methods: Using cross-sectional study, 169 participants recruited from 6 ART clinics randomly selected were interviewed to assess views on compliance, side-effects and satisfaction to new regimen. Self-reported data on compliance was complemented with patients' records at the clinics. Results: Compliance was poor in first visits on tenofovir-based regimen but gradually improved. Side-effects like dizziness, drowsiness and nightmares were reported in 56.9%, 24.9%, 23.1% of participants respectively especially during the first weeks and these negatively affected compliance (odds ratio = 1.5). Mean individual adherence was 93.3% on tenofovir-based and 85.5% on stavudine-based regimen (p Value of <0.0001). Conclusion: Tenofovir-based regimen has improved long term compliance and has the potential to eliminate suboptimal compliance rates to ARVs being a drug taken once daily. However patients still get transient side-effects especially at the beginning of taking this regimen due to efavirenz as such, regular monitoring and thorough counselling of all patients on the side effects of tenofovir-based regimen and transient nature of side effects is needed. A large scale study to be done to obtain data on long-term side-effects of tenofovir-based regimen most possibly renal impairment due to tenofovir or efavirenz-induced gynecomastia.